Current topics in robotic-assisted total hip arthroplasty: a review. Issue 2 (March 2020) - Perets, Itay; Mu, Brian H; Mont, Michael A; Rivkin, Gurion; Kandel, Leonid; Domb, Benjamin G
Total hip arthroplasty (THA) is among the most successful procedures of modern medicine, yet failures and complications continue to occur, leaving room for improvement. Robotics is a cutting-edge technology that tries to improve joint arthroplasty surgery. There is some evidence that shows that robotic-assisted THA improves implant positioning, but less is known about its effect on clinical outcomes or the rate of complications. This article reviews the literature on robotic-assisted THA to elucidate the history, advantages, disadvantages, and current clinical understanding of this procedure.